The Effect of Heuristics on the Reasoning of the Pre-Service Science Teachers on the Topic of Melting and Boiling Point - Karakoyun, Gulen Onal; Asilturk, Erol (Slovensko Kemijsko Drustvo, 2022)
The purpose of this study was to explore the effects of the heuristics on the reasoning processes of pre-service science teachers on the topic of melting and boiling point using the ten heuristic model proposed by Talanquer. In this phenomenographic study carried out in the spring semester of the 2018-2019 academic year, interviews were conducted with 30 teacher candidates enrolled in the Science Teaching Program of Firat University Faculty of Education. Participants were asked to answer three different questions during the interviews. These questions were about the ranking of some compounds according to their melting or boiling points. Six different answer patterns for each question were obtained from the answers. The findings of this study showed that students generally used shortcut strategies instead of analytical/ scientific reasoning, as all ten heuristics affected participants' reasoning. This study also revealed that although not included in the model proposed by Talanquer, periodic trends heuristic also influenced participants' reasoning about the melting and boiling point.
Keywords: Chemistry education; cognitive constraints; heuristics; melting and boiling point; reasoning; science education